Identification of Candidate Genes for the Plateau Adaptation of a Tibetan Amphipod, Gammarus lacustris, Through Integration of Genome and Transcriptome Sequencing - Jin, Shubo; Bian, Chao; Jiang, Sufei; Sun, Shengming; Xu, Lei; Xiong, Yiwei; Qiao, Hui; Zhang, Wenyi; You, Xinxin; Li, Jia; Gong, Yongsheng; Ma, Bo; et al. (Frontiers in Genetics, 2019)
The amphipod Gammarus lacustris has been distributing in the Tibetan region with well-known uplifts of the Tibetan plateau. It is hence considered as a good model for investigating stress adaptations of the plateau. Here, we sequenced the whole-genome and full-length transcriptome of G. lacustris, and compared the transcriptome results with its counterpart Gammarus pisinnus from a nearby plain. Our main goal was to provide a genomic resource for investigation of genetic mechanisms, by which G. lacustris adapted to living on the plateau. The final draft genome assembly of G. lacustris was 5.07 gigabases (Gb), and it contained 443,304 scaffolds (> 2 kb) with an N50 of 2,578 bp. A total of 8,858 unigenes were predicted in the full-length transcriptome of G. lacustris, with an average gene length of 1,811 bp. Compared with the G. pisinnus transcriptome, 2,672 differentially expressed genes (DEGs) were up-regulated and 2,881 DEGs were down-regulated in the G. lacustris transcriptome. Along with these critical DEGs, several enriched metabolic pathways, such as oxidative phosphorylation, ribosome, cell energy homeostasis, glycolysis and gluconeogenesis, were predicted to play essential roles in the plateau adaptation. In summary, the present study provides a genomic basis for understanding the plateau adaption of G. lacustris, which lays a fundamental basis for further biological and ecological studies on other resident aquatic species in the Tibetan plateau.